ANALISIS PENGAWASAN EKONOMI AL-HISBAH DAN KOMISI PENGAWAS DAN PERANNYA DALAM PERSAINGAN USAHA - Herianto Herianto; Didin Hafidhuddin; Irfan Syauqi Beik (Kasaba, 2017)
The discussion of the research focused on analyses of the supervision role of al Hisbah and KPPU which it coverage focuses on supervision object and authority between al Hisbah and KPPU. This research used two analyses approach, descriptive-analyses method and comparative-analyses method. The result of this research showed that the supervision of al Hisbah more directive to preventive action. The object of supervision including of form of transaction, supervision of commodity, supervision of economic agent and supervision on economic agent behavior. In another side, the object of KPPU supervision focused on economic agent behavior that has market power or monopolistic economic agent behavior. In the authority aspect, either al Hisbah or KPPU have the right doing controlling role to each law resource. The difference between them is laying on authority to give sanction. The authority of KPPU in apply administrative sanction is too dependent on a certain nominal that is irrelevant following the growth of fluctuation.